Play Methods in the Merdeka Curriculum at the Early Childhood Education Level (Current Research in Education: Conference Series Journal, 2024)
This study aims to provide a comprehensive review of the application of the play method, also known as ‘play freely’ or ‘merdeka bermain’, in the Merdeka curriculum at the early childhood education level in Indonesia. This research is a systematic literature review study where researchers rely on various literature sources to obtain research data and use a qualitative approach. The data collection techniques were carried out through a summary, analysis, and synthesis of several articles. Furthermore, the data collected will be analyzed using thematic analysis. The results of the study show that the play method in the Merdeka curriculum is something that is fundamental, so that it cannot be separated.